PEMILIHAN KEPALA DESA (PERBEKEL) DESA DANGIN PURI KANGIN : STUDI KEKALAHAN INCUMBENT DALAM PEMILIHAN KEPALA DESA (PERBEKEL) SERENTAK DI KOTA DENPASAR KECAMATAN DENPASAR UTARA TAHUN 2019 - Sari Krisna, Ida Bagus Gede; Andreas Noak, Piers; Erviantono, Tedi (Jurnal Nawala Politika, 2023)
This research looks at how a political actor in an incumbent position must lose to a new candidate in the simultaneous village head election (Perbekel) in Denpasar City, North Denpasar District, Dangin Puri Kangin Village. In practice, the average winner in general elections, if an incumbent candidate participates again, it is likely that the candidate probably win. The author looks at the actions of each village head candidate (Perbekel) who competed in the Dangin Puri Kangin village head election in 2019, while the names of the candidates are I Wayan Sulatra, S.T and Ir. I Gusti Ngurah Putrawan. Through several theories, namely political communication, political marketing and social capital, the author looks at the background of the incumbent candidate's loss and the key points of the winning candidates. Proximity to the village community is the main capital for candidates for village head elections, every community process in the village, especially the village of Dangin Puri Kangin causes village head candidates who are closer to the village community to have a higher chance of winning. The author sees and finds a uniqueness in this election, namely that the victory in the election does not always go to the incumbent candidate and does not rule out the possibility of a winner from outside the incumbent or someone who is not from the background of the previous government.